A folk tale narrator from Mazgirt: Süleyman Gül - Şenocak, Ebru (My University, 2002)
Text compilation and investigation is getting important day by day in Turkish folkloric studied. The studies on folk tales which were narrated according to the tradition showed that the folk tales reflect the material and spiritual features of Turkish folk culture.
Mazgi?rtli? bi?r masal anlaticisi: Süleyman Gül
Keywords: Compilation; Folk tale; Material and sipiritual culture